MS Prevalence and Patients’ Characteristics in the District of Braga, Portugal - José Figueiredo; Ângela Silva; João J. Cerqueira; Joaquim Fonseca; Paulo A. Pereira (Neurology Research International)
Multiple Sclerosis (MS) is a chronic autoimmune disease of the Central Nervous System causing inflammation and neurodegeneration. There are only 3 epidemiological studies in Portugal, 2 in the Centre and 1 in the North, and there is the need to further study MS epidemiology in this country. The objective of this work is to contribute to the MS epidemiological knowledge in Portugal, describing the patients’ epidemiological, demographic, and clinical characteristics in the Braga district of Portugal. This is a cross-sectional study of 345 patients followed in two hospitals of Braga district. These hospitals cover a resident population of 866,012 inhabitants. The data was collected from the clinical records, and 31/12/2009 was established as the prevalence day. For all MS patients, demographic characteristics and clinical outcomes are reported. We have found an incidence of 2.74/100,000 and a prevalence of 39.82/100,000 inhabitants. Most patients have an EDSS of 3 or lower and a mean age of 42 years. The diagnosis was done at mean age of 35, with RRMS being the disease type in more than 80% of patients. In this cohort, we found a female : male ratio of 1.79. More than 50% of patients are treated with Interferon β-1b IM or IFNβ-1a SC 22 μg.